2014
DOI: 10.1080/13546805.2014.928195
|View full text |Cite
|
Sign up to set email alerts
|

Moral cognition in schizophrenia

Abstract: Introduction. Disordered moral behaviour and understanding of moral rules were described early in the literature on schizophrenia; however, moral cognition has received scant attention in spite of a large literature focused on social cognitive impairments and violent behaviour in schizophrenia. Methods. We conducted a narrative synthesis of the literature on violence, moral judgement and schizophrenia. Results. Initial empirical research into moral cognition in schizophrenia did not fully account for the basic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 72 publications
0
10
1
Order By: Relevance
“…They exhibit reduced brain activity in right hypothalamus and right superior temporal gyrus region. Same misbehaviour patterns have also been observed in autistic children in some cases which might be associated with poor theory of mind [98]. These two disorders often overlap in their identity and common in males.…”
Section: Biological Causes For Autism:-31 Schizophreniamentioning
confidence: 94%
See 1 more Smart Citation
“…They exhibit reduced brain activity in right hypothalamus and right superior temporal gyrus region. Same misbehaviour patterns have also been observed in autistic children in some cases which might be associated with poor theory of mind [98]. These two disorders often overlap in their identity and common in males.…”
Section: Biological Causes For Autism:-31 Schizophreniamentioning
confidence: 94%
“…Several studies reported that individuals involved in violence and aggressive behaviour suffers from psychosis [91][92][93][94] in most cases and it has also found that their background is associated with factors such as sexual abuse, low income, use of drugs and alcoholism [91,92,[95][96][97]. Affected individuals showed poor speech and reasoning skills which might be a neurocognitive deficit [98]. They exhibit reduced brain activity in right hypothalamus and right superior temporal gyrus region.…”
Section: Biological Causes For Autism:-31 Schizophreniamentioning
confidence: 99%
“…People with schizophrenia obtained lower scores, focusing their explanations on “power, status and possessions, compared to concepts of equality, reciprocity and trust” found in control participants (Benson, 1980, p. 676). According to McGuire et al (2014) this worst performance was linked to the inability of these individuals to correctly make inferences, required from the MJI, about the mental states of the agents involved. Interestingly, Langdon et al (2014) examined 43 patients with schizophrenia and healthy controls on Theory of mind tests and on a novel test of social judgment (adapted from autism research – Ellis et al, 1994).…”
Section: Theory Of Mind and Moral Decision-makingmentioning
confidence: 99%
“…Benson, 1980). In our review (McGuire, Langdon, & Brüne, 2014), we argued that this early research was problematic due to its reliance on data collected using Kohlberg's Moral Judgement Interview (MJI; Colby et al, 1987). The MJI requires participants to generate justifications of their judgements of moral dilemmas and relies on memory for dilemma story details, and explicit elucidation of reasoning processes.…”
Section: Introductionmentioning
confidence: 97%